Non-operative management of water injection injury to the neck - Nader Tehrani; Afshin A. Anoushiravani; Avinash Bhakta; Roman V. Petrov; Marcel Tafen; Sharon Samuels (Elsevier, 2016)
Although rarely reported in the pediatric population, high-pressure injection injuries are a common occurrence in adult industrial workers. These injuries commonly exhibit physiologic patterns consistent with direct kinetic trauma, localized substance toxicity, and in later stages infection. The majority of reported cases describe injection injuries caused by caustic substances at high pressures frequently necessitating debridement. In this case, we present a 12-year old boy who sustained a Zone III penetrating neck injury after running in front of a commercial pressure washer. In our case presentation there was concern for vascular and aero-digestive injuries; however, following physical examination and advanced imaging, expectant management was successfully adopted.